Psychometric validation of the 20-item K-DOCS in Chinese adolescents: a multi-method approach - Cui-Hong Cao; Xue-Lian Wang; Yin-Ping Ji; I-Hua Chen (Scientific Reports)
Abstract Creativity is crucial for addressing new world challenges. The Kaufman Domains of Creativity Scale, a widely used self-report scale, assesses distinct creativity facets but lacks validation in adolescents under 18 and is limited by classical test theory (CTT). This study evaluated the psychometric properties of the 20-item Kaufman Domains of Creativity Scale (20-K-DOCS) in Chinese adolescents aged 15–18. 3,079 adolescents completed the 20-K-DOCS. CTT, Rasch analysis, and Exploratory Structural Equation Modeling (ESEM) were used to assess reliability and various types of validity. Concurrent validity was examined by correlating 20-K-DOCS scores with Creative Self-Efficacy (CSE). The 20-K-DOCS demonstrated excellent internal consistency (McDonald’s omega: 0.91–0.95 per subscale). Rasch analysis supported item validity and optimal functioning. The oblique five-factor model and the ESEM five-factor model indicated satisfactory model fit. ESEM revealed convergent validity and addressed high factor correlations, improving discriminant validity. Significant positive correlations were found between 20-K-DOCS and CSE, particularly in Artistic and Scholarly Creativity. The 20-K-DOCS is a reliable and valid measure of domain-specific creativity in Chinese adolescents. Findings emphasize the importance of domain-specific approaches to creativity assessment and suggest the potential for developing a more concise scale version.